Enhancing nursing students' cultural awareness through Community of Inquiry‐guided online 'Internationalization at Home' strategies-An intervention study - Siu Ling Chan; John Tai Chun Fung; Naomi Takemura; Pui Hing Chau; Jay Jung Jae Lee; Hye Ri Choi; Wai Hin Wan; Harrison Withrow; Chia‐Chin Lin (Wiley, 2024)
Abstract Aim Internationalization at Home (IaH) strategies play an important role in nursing curricula to enhance nursing students' cultural awareness in the globalized world. The Community of Inquiry (CoI) is a theoretical framework for the optimal design of online learning environments to support critical inquiry and discourse among students and teachers. To optimise nursing students' online cultural awareness learning experiences, it was timely to develop online IaH strategies based on a sound theoretical model. This study aimed to examine the effectiveness of CoI‐guided online IaH strategies on enhancing the cultural awareness of nursing undergraduates who enrolled in a community nursing course. Design This was an interventional pre‐test post‐test study. Method One hundred and six nursing undergraduates who enrolled in the course participated in the study. The online IaH strategies were developed focusing on the interactions of teaching presence, cognitive presence and social presence of CoI framework and they were integrated into the course. A previously validated Cultural Awareness Scale was adopted for pre‐post evaluation. Higher scores indicate greater cultural awareness. Results The results showed that there was a significantly higher total score of cultural awareness of participating students at post‐online IaH strategies. To be effective, aligning CoI‐guided online IaH strategies with course content, pedagogy and assessment was shown to be significant. The inclusion of technological elements in related strategies was also critical to engage student learning. The positive change on the total score of cultural awareness suggested the effectiveness of the deployed strategies. In this ever‐changing educational landscape, it may provide insights to educators regarding considering online IaH strategies with theoretical underpinning for curriculum planning and design.